Feminisme Dan Feminisme Islam Dalam Karya Sastra: (PENDEKATAN SOSIOLOGI SASTRA TERHADAP NOVEL DI INDONESIA) - Wirayudha Pramana Bhakti (UIN K.H. Abdurrahman Wahid Pekalongan, 2018)
This paper examines the feminism and feminism of Islam in the novel in Indonesia. The approach used is the sociology of literature, which aims to describe the problems of feminism with regard to social, cultural, and belief systems of society. Feminism has an important role and is one of the novel appeal. Feminism in the novel rejects all forms of discrimination against women. The concept of feminism in the novel in Indonesia shifts to Islamic feminism, namely the concept of gender equality that refers to the principles of Islamic teachings. Through the novel Islamic feminism, Muslim authors want to convey some message of da'wah. First, Islamic feminism is gender equality derived from Al Quran and Hadith. Second, Islamic feminism is one of Muslim women's image which is related to morality and attitude of Muslim woman when faced with problem.